2009
DOI: 10.1590/s0103-73312009000400015
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian legislation for functional foods and the interface with the legislation for other food and medicine classes: contradictions and omissions

Abstract: Functional foods are generally defined as foods that, due to their physiologically active substances, benefit health in addition to providing basic nourishment. As Brazilian legislation does not provide a definition for functional foods, the only possible actions is to claim that some foods have functional health proprieties. Based on a review of legislation, this paper discusses not only the lack of transparency in relation to the categories of products classified as foods and medicinal plants, but also the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
7
0
9
Order By: Relevance
“…The analysis of the country of origin of each depositor can be observed in Figure 3 At the same time, functional properties and/or health claims on a food label are tools that allow the consumer to know the possible benefits the food can offer. However, it is necessary to clearer rules for the industry so that the consumer is not deceived by false cure promises (SILVEIRA et al, 2009) Among the documents identified in the survey, 55% are related to the field of microorganisms or enzymes and their compositions (C12N); 18% are in the area of food, food products and non-alcoholic beverages and preparations for medical purposes (A61K and A23C, respectively); and 9% are in the area of dairy products (A61K) (Figure 4). A61K (preparations for medical, dental or hygienic purposes) and A23C which is part of Section A -for human needs, linked to class 23 related to food or food products; not covered by other classes and subclass C dairy products, ex.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the country of origin of each depositor can be observed in Figure 3 At the same time, functional properties and/or health claims on a food label are tools that allow the consumer to know the possible benefits the food can offer. However, it is necessary to clearer rules for the industry so that the consumer is not deceived by false cure promises (SILVEIRA et al, 2009) Among the documents identified in the survey, 55% are related to the field of microorganisms or enzymes and their compositions (C12N); 18% are in the area of food, food products and non-alcoholic beverages and preparations for medical purposes (A61K and A23C, respectively); and 9% are in the area of dairy products (A61K) (Figure 4). A61K (preparations for medical, dental or hygienic purposes) and A23C which is part of Section A -for human needs, linked to class 23 related to food or food products; not covered by other classes and subclass C dairy products, ex.…”
Section: Resultsmentioning
confidence: 99%
“…3,7,[10][11][12]17 Alimentos que apresentam propriedades funcionais no Brasil são definidos com base no "papel metabólico ou fisiológico desempenhado por eles no crescimento, desenvolvimento, manutenção e/ou funções normais do corpo humano". 18…”
Section: Discussionunclassified
“…O grupo T apresentou força máxima no teste biomecânico em comparação ao grupo C. Os demais parâmetros não apresentaram diferença significativa entre os grupos; entretanto, o grupo T registrou força máxima (+10%) e resistência à ruptura (+6%) maiores do que o grupo C, aos 90 dias de vida. A preservação da força óssea é influenciada pela ingestão adequada de cálcio e vitamina D. No entanto, outros nutrientes, tais como potássio, magnésio, bem como as vitaminas B, K e C desempenham um papel fundamental na saúde óssea 18,19. A espécie Colocasia esculenta é rica em nutrientes capazes de influenciar a formação óssea,[19][20][21][22] tais como o cálcio, que desempenha papel fundamental nos processos de pico de massa óssea e aquisição de força; e o magnésio, que é essencial para o crescimento e saúde óssea 19,20.…”
unclassified
“…A legislação brasileira não contempla a definição sobre alimentos funcionais, mencionando, apenas, que determinados alimentos possuem propriedades funcionais. Um produto pode ser registrado, tanto nas categorias de Novos Alimentos e Ingredientes quanto em Substâncias Bioativas e Probióticos Isolados com Alegação de Propriedades Funcional e/ou de Saúde (SILVEIRA et al, 2009). Assim sendo, emerge um desafio para regulamentação brasileira de alimentos funcionais.…”
Section: Considerações Finaisunclassified